Serena Williams: Tennis Champion, Sports Legend, and Cultural Heroine - Corbett, Merlisa Lawrence, (Rowman & Littlefield Publishers, 2020)
Record-breaking, trend-setting, polarizing, and controversial, Serena Williams often sparks conversation and debate. The 23-time Grand Slam champion has a team, an entourage, celebrity groupies, and a band of fans who call themselves “Serena’s army.” When not winning titles, Williams finds time to run her own fashion line, endorse luxury and financial brands, and fund schools for girls in Africa and Jamaica. Serena Williams transcends sports. More than a biography, Serena Williams: Tennis Champion, Sports Legend, and Cultural Heroine not only tells the story of her upbringing and remarkable career but also looks at Williams as a sports pioneer. Merlisa Lawrence Corbett explores Williams’ influence on cultural and political issues such as body shaming, gender equality, and racism in sports and society. Corbett also analyzes Williams’ impact on discussions of feminism, the sports celebrity, and the marketing of female athletes. Williams is one of the most intriguing and influential figures in sports, and this book is the first to provide a fully-rounded portrait of a tennis icon.